Chariots of fire [videorecording (DVD)] - Welland, Colin; Farrell, Nicholas; Havers, Nigel, 1949-; Charleson, Ian; Cross, Ben; Gerroll, Daniel; Holm, Ian, 1931-2020; Gielgud, John, 1904-2000; Anderson, Lindsay, 1923-1994; Davenport, Nigel; Campbell, Cheryl; Krige, Alice, 1954-; et al. (Academy Award (Oscar) Winner: Best Picture., 2010)
The story, told in flashback, of two young British sprinters competing for fame in the 1924 Olympics. Eric, a devout Scottish missionary runs because he knows it must please God. Harold, the son of a newly rich Jew runs to prove his place in Cambridge society. In a warmup 100 meter race, Eric defeats Harold, who hires a pro trainer to prepare him. Eric, whose qualifying heat is scheduled for a Sunday, refuses to run despite pressure from the Olympic committee. A compromise is reached when a nobleman allows Eric to compete in his 400 meter slot. Eric and Harold win their respective races and go on to achieve fame as missionary and businessman/athletic advocate, respectively.